Phenological and molecular studies on the introduced seaweed Dictyota cyanoloma (Dictyotales, Phaeophyceae) along the Mediterranean coast of the Iberian Peninsula - ARAGAY, J.; VITALES, D.; GÓMEZ GARRETA, A.; RIBERA SIGUAN, M. A.; STEEN, F.; DE CLERCK, O.; GARNATJE, T.; RULL LLUCH, J. (Mediterranean Marine Science, 2016)
Dictyota cyanoloma, a distinctive brown algal species characterized by a blue-iridescent margin, was recently reported as an introduced species in the Mediterranean Sea (Steen et al., 2016) but little is known about its distribution dynamics, morphological plasticity and genetic structure. In the present integrative study, we evaluate its past and present occurrence along the Mediterranean Iberian coast, assess the species’ phenology in Palamós (Girona, Spain) and analyze the haplotype diversity by sequencing 49 individuals from nine sampling sites for different chloroplast and mitochondrial DNA regions. Although D. cyanoloma currently occurs along the Mediterranean Iberian coast (in 19 of 36 localities sampled between Algeciras and Llançà, mostly in marinas and harbour environments), we were not able to find any herbarium material of this species (at BCN-Phyc and MA) predating the year 1987. In Palamós, D. cyanoloma is present all through the year, with a maximum development in winter and a minimum in summer. Fertile specimens are absent during summer (July and August). Sporophytes are dominant from January to June and dioecious gametophytes were found only in February, March and June. Information about the antheridia, which has never been described before, is provided. Two chloroplast and three mitochondrial haplotypes were observed, indicating that multiple introductions of D. cyanoloma occurred in the study area. Additionally, the genetic structure suggests that spread did not occur through simple advancing wave fronts but by several long-distance dispersal events. Further studies employing microsatellite markers could potentially offer a better resolution to unravel expansion and colonisation dynamics of D. cyanoloma in the Mediterranean Sea.